Second-line treatment after docetaxel, cisplatin and 5-fluorouracil in metastatic squamous cell carcinomas of the anus. Pooled analysis of prospective Epitopes-HPV01 and Epitopes-HPV02 studies. (February 2022) - Stouvenot, Morgane; Meurisse, Aurélia; Saint, Angélique; Buecher, Bruno; André, Thierry; Samalin, Emmanuelle; Jary, Marine; El Hajbi, Farid; Baba-Hamed, Nabil; Pernot, Simon; Kaminsky, Marie-Christine; Bouché, Olivier; et al.
Abstract: Background: Squamous cell carcinoma of the anus (SCCA) is a rare disease often diagnosed at a localised stage. For locally advanced recurrence or metastatic disease, DCF (docetaxel, cisplatin, 5-fluorouracil) demonstrated high efficacy and became one of the standard regimens. However, there is no standard of care in the second line. Patients and methods: In the Epitopes-HPV01 and Epitopes-HPV02 prospective trials, 115 patients with advanced SCCA were treated with a DCF regimen in the first line. In these studies, second-line data were registered per protocol. Results: After a median follow-up of >40 months, at progression, 73 patients received a second-line (L2) treatment. In this L2 population, median overall survival (mOS) was 13.5 months (95%CI 9.4–19.8), and median progression-free survival (mPFS) was 5.7 months (3.4–7.3) in L2. Fourteen patients presented an oligometastatic progression and were treated with an ablative treatment (surgery or radiotherapy); mOS was 48.3 months (NE–NE), and mPFS was 31.3 months (23.2–NE). Fifty-nine patients received a systemic treatment (chemotherapy or immunotherapy); mOS was 11 months (8.4–15.4) and mPFS was 4.9 months (3.3–7). The most frequent chemotherapy regimens were the reintroduction of DCF, paclitaxel, FOLFIRI and mitomycin plus fluoropyrimidine. No significant difference was observed between regimens (p = 0.26). Six patients received anti-PD1/L1-based immunotherapy. Conclusion: Second-line treatments are effective in patients with SCCA. Ablative treatment is feasible and is probably the best option for patients with oligometastatic progression. If this is not possible, systemic therapy by an anti-PD1/L1 immunotherapy or chemotherapy can be recommended. Reintroduction of DCF, paclitaxel, FOLFIRI or mitomycin-C plus fluoropyrimidine are possible options. Highlights: There is no validated standard treatment in second-line in advanced squamous cell carcinoma of the anus. Curative-intent ablative treatment should be recommended whenever is possible. Chemotherapy in second-line is a valid option. Modified docetaxel, cisplatin and 5-fluorouracil reintroduction, paclitaxel, FOLFIRI, or mitomycin-C + 5-fluorouracil can be recommended. Anti-programmed cell death protein 1 (PD1) immunotherapy demonstrated some efficacy in second-line.